PENYIDIKAN TINDAK PIDANA PRAKTEK KEDOKTERAN (MALAPRAKTIK KEDOKTERAN) DI POLDA SULAWESI SELATAN: INVESTIGATION OF CRIMINAL ACTION OF MEDICAL PRACTICE (MEDICAL MALAPRACTIC) IN THE POLICE OF THE SOUTH SULAWESI REGION - Astaman; Mas, Marwan; Oner, Basri (Faculty Of Law Bosowa University, 2020)
This study aims to determine the implementation of investigations into medical practice crime (medical malpractice) in the South Sulawesi Regional Police and also know the factors that influence the investigation of medical practice criminal acts in the South Sulawesi region. The study was conducted at the South Sulawesi Regional Police Headquarters (Mapolda Sulsel) Directorate of Special Criminal Investigation, South Sulawesi Regional Police located in Makassar, with the Field Research method by obtaining data by conducting direct research in the field through interviews or direct talks with Investigators, and also Literature Research Method This method is an attempt to obtain secondary data through reading material in the form of scientific writings, legislation, theories of experts through various media. The results of this study indicate the implementation of investigations into medical practice crimes based on Article 5 of the Criminal Procedure Code, Law Number 2 of 2002 concerning the Republic of Indonesia Police, Police Headquarters Exchange Number 6 of 2019 and Regulations on Kabareskrim Number 3 of 2014 plus Law Number 29 of 2004 concerning Medical Practices, Law No 36 of 2009 concerning health, Law Number 36 of 2014 concerning health workers and internal regulations on other medicine for the handling of medical malpractice cases is the basis for investigators and auxiliary investigators perform a series of actions to find 2 legal preliminary evidence, to search for and find criminal acts. or not, the implementation of investigations into medical practice in golongka in very difficult cases that require science-type crame investigation in handling, this case requires many scientific disciplines and many experts who are involved in the disclosure of the case whether it is from medical experts and criminal law , this case is classified as a case that is considered to be a very difficult case.